A Comparative Bio-Evaluation and Chemical Profiles of Calendula officinalis L. Extracts Prepared via Different Extraction Techniques - Gunes Ak; Gokhan Zengin; Kouadio Ibrahime Sinan; Mohamad Fawzi Mahomoodally; Marie Carene Nancy Picot-Allain; Oguz Cakır; Souheir Bensari; Mustafa Abdullah Yılmaz; Monica Gallo; Domenico Montesano (Applied Sciences, 2020)
Calendula officinalis L., (marigold), well known for its medicinal properties, has been extensively studied for its therapeutic properties. Nonetheless, as far as the literature could establish, no study has attempted to comparatively assess the biological (antioxidant and enzyme inhibitory potential) of the flowers, leaves, and roots of C. officinalis extracted using conventional (maceration and Soxhlet extraction (SE)) and non-conventional extraction (homogenizer (HAE) and ultrasound (UAE) assisted extraction) techniques. The detailed phytochemical profile of each extract along with the concentration of specific bioactive compounds has also been established. Total phenolic content was highest for the flower extracts while flavonoid content was highest in the leaf extracts. Phytochemical profiling showed that the extraction method influenced the phytochemical composition of the extract. Nicotiflorin was identified in the flower extracts only while amentoflavone occurred only in the roots, inferring that the occurrence of bioactive compounds varies within a plant. The flower extracts showed highest antioxidant potential while the roots extracts were potent inhibitors of cholinesterase and tyrosinase. This study provides valuable data on the influence of extraction techniques on the recovery of bioactive compounds from plants. In an endeavor to scale-up extraction from plant considering the more efficient extraction method is of paramount importance. Moreover, the study highlighted the necessity to thoroughly examine the biological activities of various parts of a plant obtained via different extraction protocols.